Khalayak Media Baru - Malau, Ruth (Universitas Semarang, 2011)
New media era brought a complex story about what is media audience nowadays. The situasion in this postmodernism world is quite different because audience has become more active in consuming the new media. The one that once known as mass audience has now dissapeared because of the popularity of the new media. When audience is no longer a mass, fandom emerge as one of the most known as the new media audience.